PEMBUATAN PETA ANCAMAN EROSI DENGAN METODE UNIVERSAL SOIL LOSS EQUATION (USLE) Studi kasus: Sub DAS Keduang, Jawa Tengah - , DIAN KRISTIANA T ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Keduang Sub Watershed Area is part of Solo Watershed Area,it ends in Gadjah Mungkur Reservoir, Wonogiri. This research was aimed to predict the erosion danger level at Keduang Sub Watershed Area based on the Universal Soil Loss Equation formula, by applying a Geographical Information System analysis. Based on the formula, we used four types of maps, in examples rainfall, soil, slope, and land cover maps. On each map, classification was done to get four to five classes based on a specific factor standard. An overlay process was done to get the final result, in example erosion danger level prediction. The level was classified into five categories those were very heavy, heavy, medium, light, and very light. The results showed that Keduang Sub Watershed Area actual erosion prediction is amount 227,192 ton/Ha/th. The results can be used as a database to make a good planning watershed area management.